2016
DOI: 10.4028/www.scientific.net/kem.711.564
|View full text |Cite
|
Sign up to set email alerts
|

Fire Performance of Columns Made of Normal and High Strength Concrete: A Comparative Analysis

Abstract: Abstract. The use of high strength concrete (HSC) in multi-story buildings has become increasingly popular. Selection of HSC over normal strength concrete (NSC) allows for reducing the dimensions of the columns sections. However, this reduction has consequences on the structural performance in case of fire, as smaller cross sections lead to faster temperature increase in the section core. Besides, HSC experiences higher rates of strength loss with temperature and a higher susceptibility to spalling than NSC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the end, the relationship between the applied load ratio and the fire resistance time is obtained for each column. More details are given in (Gernay, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In the end, the relationship between the applied load ratio and the fire resistance time is obtained for each column. More details are given in (Gernay, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The microstructure of the type of concrete may play a great role in modifying the thermal properties of concrete (Luccioni et al 2003). Moreover, it is reported that HSC performs worse than NSC in fire because of its constituent materials (Gernay 2016). The relative loss of compressive strength with temperature and the higher probability occurrence of explosive spalling are two important factors in HSC that reduces the fire performance of this material (Kodur 2014).…”
Section: Introductionmentioning
confidence: 99%